Lipid Nanoparticles Deliver the Therapeutic VEGFA mRNA In Vitro and In Vivo and Transform Extracellular Vesicles for Their Functional Extensions. Issue 12 (19th February 2023) - Nawaz, Muhammad; Heydarkhan‐Hagvall, Sepideh; Tangruksa, Benyapa; González‐King Garibotti, Hernán; Jing, Yujia; Maugeri, Marco; Kohl, Franziska; Hultin, Leif; Reyahi, Azadeh; Camponeschi, Alessandro; Kull, Bengt; Christoffersson, Jonas; et al.
Abstract: Lipid nanoparticles (LNPs) are currently used to transport functional mRNAs, such as COVID‐19 mRNA vaccines. The delivery of angiogenic molecules, such as therapeutic VEGF‐A mRNA, to ischemic tissues for producing new blood vessels is an emerging strategy for the treatment of cardiovascular diseases. Here, the authors deliver VEGF‐A mRNA via LNPs and study stoichiometric quantification of their uptake kinetics and how the transport of exogenous LNP‐mRNAs between cells is functionally extended by cells' own vehicles called extracellular vesicles (EVs). The results show that cellular uptake of LNPs and their mRNA molecules occurs quickly, and that the translation of exogenously delivered mRNA begins immediately. Following the VEGF‐A mRNA delivery to cells via LNPs, a fraction of internalized VEGF‐A mRNA is secreted via EVs. The overexpressed VEGF‐A mRNA is detected in EVs secreted from three different cell types. Additionally, RNA‐Seq analysis reveals that as cells' response to LNP‐ VEGF‐A mRNA treatment, several overexpressed proangiogenic transcripts are packaged into EVs. EVs are further deployed to deliver VEGF‐A mRNA in vitro and in vivo. Upon equal amount of VEGF‐A mRNA delivery via three EV types or LNPs in vitro, EVs from cardiac progenitor cells are the most efficient in promoting angiogenesis per amount of VEGF‐A protein produced. Intravenous administration of luciferase mRNA shows that EVs could distribute translatable mRNA to different organs with the highest amounts of luciferase detected in the liver. Direct injections of VEGF‐A mRNA (via EVs or LNPs) into mice heart result in locally produced VEGF‐A protein without spillover to liver and circulation. In addition, EVs from cardiac progenitor cells cause minimal production of inflammatory cytokines in cardiac tissue compared with all other treatment types. Collectively, the data demonstrate that LNPs transform EVs as functional extensions to distribute therapeutic mRNA between cells, where EVs deliver this mRNA differently than LNPs. Abstract : The study shows that a fraction of LNP‐mRNA that is cell‐endocytosed can be sent to other cells via the secretion of extracellular vesicles (EVs). LNPs transform these EVs as functional extensions to distribute therapeutic mRNA between cells.Importantly, EVs can be isolated such as from cardiac progenitor cells (CPC‐EVs), and thus utilized for mRNA delivery in vivo. Upon mRNA delivery to cardiac tissue, CPC‐EVs cause less expression of inflammatory cytokines, compared to other vehicles used.